Sperm morphology: What implications on the assisted reproductive outcomes?. (28th August 2020) - Cito, Gianmartin; Picone, Rita; Fucci, Rossella; Giachini, Claudia; Micelli, Elisabetta; Cocci, Andrea; Falcone, Patrizia; Minervini, Andrea; Carini, Marco; Natali, Alessandro; Coccia, Maria E.
Abstract: Objective: To evaluate the impact of sperm morphology (SM) on laboratory and pregnancy outcomes in conventional intracytoplasmic sperm injection (c‐ICSI) cycles, using the egg donation model to minimize female confounding variables. Materials and methods: We retrospectively collected data of oocyte donation cycles from October 2016 to February 2020. Median seminal parameters, total (1‐2‐3PN) fertilization rate (FR), 2PN FR, cleavage rate (CR), implantation rate (IR), pregnancy rate (PR), miscarriage rate (MR), and live birth rate (LBR) were collected. The study population was divided into three groups: Group 1 with SM < 4%, Group 2 with SM between 4% and 6%, and Group 3 with SM > 6%. Results: Of 741 fresh ICSI cycles and 4507 warmed oocytes were included. Male age was 46.0 (31.0‐72.0) years, and recipients' age was 44.0 (29.0‐54.0) years. Normal SM was 5.0% (1.0%‐15.0%). Male age was negatively correlated with normal SM ( P  = .002; Rho −0.113). Oocyte survival rate was 83.3% (16.7%‐100.0%). Total FR was 75.0% (11.1%‐100.0%), 2PN FR was 66.7% (11.1%‐100.0%) %, and CR was 100% (0.0%‐100%). Comparing samples with SM > 6% and those with SM < 4%, 2PN FR was significantly higher in the first group ( P  = .04). No significant associations were found among groups in terms of CR. IR was 27.7%, resulting significantly higher when normal SM was > 6% ( P  < .01). Clinical PR was 36.0%, MR was 23.9%, and LBR was 25.9%. PR and LBR were significantly higher in samples with normal SM > 6%, compared to other groups ( P  = .02 and P  < .01, respectively). Conclusions: Although c‐ICSI technique allows the embryologist to select the best quality spermatozoa, male factor plays a key role in achieving successful assisted reproductive outcomes. Normal SM has been shown to have implications not only for laboratory outcomes, in terms of fertilization, but also for clinical findings, as regards implantation, pregnancy, and live birth.